A low oxygen consumption pneumatic ventilator for emergency construction during a respiratory failure pandemic - John Dingley (Anaesthesia, 2010)
The UK influenza pandemic plan predicts up to 750,000 additional deaths with hospitals prioritising patients against inadequate resources. We investigated three prototype low-cost, gas-efficient, pneumatic ventilators in a test lung model at different compliance and rate settings. Mean (SD) oxygen consumption was 0.913 (0.198) and 1.119 (0.267) l.min(-1) at tidal volumes of 500 ml and 700 ml respectively. Values of F(I)o(2) increased marginally as lung compliance reduced, reflecting the increased ventilator workload and consequent increased enrichment of breathing gas by waste oxygen from the pneumatic mechanism. We also demonstrated that a stable nitric oxide concentration could be delivered by this design following volumetric principles. It is possible to make a gas-efficient ventilator costing less than 200 pounds from industrial components for use where oxygen is available at 2-4 bar, with no pressurised air or electrical requirements. Such a device could be mass-produced for crises characterised by an overwhelming demand for mechanical ventilation and a limited oxygen supply.